THE ROLES OF THE TOURISM SECTOR IN THE LABOR ABSORPTION IN THE TRADE, RESTAURANT, AND ACCOMMODATION SECTORS IN BALI PROVINCE IN 2013-2017 - Ghendis Saras Zandy; Lely Ratwianingsih (Journal of Applied Economics in Developing Countries, 2019)
The purpose of this study was to analyze the effects of GRDP, regency/city (regional) minimum wage, the number of hotels and restaurants, and the number of tourist attractions on the labor absorption in the trade, restaurant, and accommodation sectors. Bali was selected due to its potential for cultural diversity and tourist attractions. This quantitative study used panel data with nine regencies/cities in Bali Province in 2013-2017. The best model applied in this study was the Fixed Effect Model. The results of the analysis show that all independent variables had simultaneous effects on the given variables. The results of the partial analysis confirmed that GRDP had a significant negative effect, regency/city minimum wage, and the number of hotels and restaurants had a significant positive effect, while the number of tourist attractions did not produce any effects on labor absorption. It is suggested that the local governments and related parties encourage tourism activities and improve the quality of the workforce. Keywords: Tourism, Labor Absorption, GRDP, Regency/City Minimum Wage, The Number of Hotels and Restaurants, The Number of Tourist Attractions